Exposomics: a review of methodologies, applications, and future directions in molecular medicine - Wan, Melissa; Simonin, Elisabeth M; Johnson, Mary Margaret; Zhang, Xinyue; Lin, Xiangping; Gao, Peng; Patel, Chirag J; Yousuf, Aroub; Snyder, Michael P; Hong, Xiumei; Wang, Xiaobin; Sampath, Vanitha; et al. (EMBO molecular medicine, 2025)
The exposome is the measure of all the exposures of an individual in a lifetime and how those exposures relate to health. Exposomics is the emerging field of research to measure and study the totality of the exposome. Exposomics can assist with molecular medicine by furthering our understanding of how the exposome influences cellular and molecular processes such as gene expression, epigenetic modifications, metabolic pathways, and immune responses. These molecular alterations can aid as biomarkers for the diagnosis, disease prediction, early detection, and treatment and offering new avenues for personalized medicine. Advances in high throughput omics and other technologies as well as increased computational analytics is enabling comprehensive measurement and sophisticated analysis of the exposome to elucidate their cumulative and combined impacts on health, which can enable individuals, communities, and policymakers to create programs, policies, and protections that promote healthier environments and people. This review provides an overview of the potential role of exposomics in molecular medicine, covering its history, methodologies, current research and applications, and future directions. In this review, K. Nadeau and colleagues discuss the emerging field of exposomics, including its methodologies and applications in molecular medicine. They explore how advances in technology and analytics enable the study of environmental exposures, their molecular impacts, and their potential to improve personalized medicine and public health.